IMPLEMENTATION OF RSA AND ELGAMAL ALGORITHMS FOR SECURING VIDEO FILES - Afif Abdillah; Akim M.H. Pardede; Ramadhani (Journal of Data Analytics, Information, and Computer Science, 2025)
The rapid development of information and communication technology has made it an essential part of modern life. Among its many applications, the transmission of video data has become increasingly common, but ensuring its confidentiality and integrity remains a major challenge. Video messages, particularly those containing personal or sensitive information, are vulnerable to interception and unauthorized access when transmitted over public networks. To address this issue, cryptographic methods are employed to transform the original video file (plaintext) into an encrypted form (cipher text), which can only be decrypted with the correct key. Previous studies highlight that while RSA offers a relatively simple encryption mechanism, it is often considered insufficient as a standalone approach. Therefore, this study investigates the combined implementation of RSA and ElGamal algorithms to enhance video file security by leveraging the strengths of both techniques. The experimental results demonstrate that the integration of RSA and ElGamal algorithms can successfully encrypt and decrypt video files, ensuring data confidentiality. Encrypted videos cannot be accessed without the appropriate private key, which safeguards sensitive content from unauthorized parties. Furthermore, RSA is found to be simpler to apply, while ElGamal provides stronger security based on the discrete logarithm problem. Overall, the proposed system effectively maintains both the confidentiality and integrity of video files, thereby improving the security of multimedia data transmission.